From Afropea to the Afro-Atlantic : a study of four novels by Léonora Miano and Fatou Diome - (:unkn) unknown (My University, 2021)
Recent research in the field of Francophone African literature has suggested that contemporary Sub-Saharan authors living and writing in Europe present in their works a fundamentally devalorising image of their continent of origin. This thesis considers the textual representation of the African continent and Africanicity in the novels of two contemporary Sub-Saharan authors writing in French on Africa from Europe – Léonora Miano from Cameroon and Fatou Diome from Senegal. The study seeks to determine whether Diome and Miano present in their texts a devalorising image of Sub-Saharan Africa and Africanicity more broadly or, conversely, whether there is evidence in their fiction of a commitment to a project of Afro-identitarian revalorisation. This study demonstrates a marked evolution across the literary production of Miano and Diome through the theoretical concept of Afro-diasporic consciousness informed and developed upon by theory drawn from postcolonial, diaspora and feminist literary studies. It comparatively analyses Diome’s Le Ventre de l’Atlantique (2003) and Miano’s L’intérieur de la nuit (2005) followed by Diome’s Celles qui attendent (2010) and Miano’s Les aubes écarlates: Sankofa cry (2009) to reveal the authors’ increasingly ardent commitment to rehabilitating and revalorising contemporary Africanicity through fiction. This revalorisation is shown to be dependent on movement beyond the bounds of binary and colonially-referential Afropea and towards transnational engagement with Africa’s Black Atlantic diaspora.
Keywords: African Research